Mediation as a consumer dispute resolution mechanism / Hasmah Nordin and Siti Mardhiyyah Zamani - Nordin, Hasmah; Zamani, Siti Mardhiyyah (2012)
This is a study on mediation as a mechanism for settling consumer disputes. The main objective of the study is to identify the suitability of mediation as a mechanism to be implemented in Malaysia as a consumer redress mechanism. The study will start by discussing the main weaknesses of the court system and the Tribunal for Consumer Claims which lead to the use of alternative methods to resolve. For the purpose of this project paper, focus will only be given to mediation. This study will look at the new Act, which is the Mediation Act 2012, and its provisions in settling consumer disputes. The benefits and suitability of applying mediation in Malaysia will also be examined. In doing this study, comparison will be made to other forms of Alternative Dispute Resolution. In addition this study will also provide an evaluation of the application of mediation in various countries in settling disputes as well as the impact of application of mediation to consumer disputes. Lastly, the research will suggest ways to improve mediation as a method of settling consumer disputes in Malaysia.